Implications of rainfall for agricultural and urban development of Eldoret, Kenya - E. Ofori- Sarpong (Faculty of Geography, Universitas Gadjah Mada, 1991)
This paper examines the role of rainfall in the urban development of Kenya. The rainfall characteristics have been analysed and their influence on agricultural and urban development assessed. It is noted that since Eldoret is one of the rapidly expanding towns in Kenya located in highly potential agricultural region, variability of rainfall and drought can seriously affect urban development as farmers in the hinterland will abandon their farms and migrate to the town thus creating food shortage. Secondly, in times of drought, the water supply problems in the town will be exacerbated as it depends on surface water source. The tempo of rural-urban migration will be speeded up and this will create more socio-economic problems.